Current Perspectives of the Australian Knee Society on Rehabilitation and Return to Sport After Anterior Cruciate Ligament Reconstruction - Ebert, Jay; Webster, Kate; Edwards, Peter; Joss, Brendan; D'Allessandro, Peter; Janes, Greg; Annear, Peter (Human Kinetics Publishers Inc., 2019)
Context: The importance of rehabilitation and evaluation prior to return to sport (RTS) in patients undergoing anterior cruciate ligament reconstruction has been reported. Objective: This study sought to investigate current perspectives of Australian orthopedic surgeons on rehabilitation and RTS evaluation. Design: Survey. Participants: Members of the Australian Knee Society. Main Outcome Measures: A 14-question survey was disseminated to Australian Knee Society members (orthopedic surgeons) to investigate (1) preferred graft choice, (2) estimated retear rate, (3) importance of preoperative and postoperative rehabilitation, and (4) preferred timing of RTS and evaluation prior to RTS discharge. Results: Of all 85 Australian Knee Society members contacted, 86% (n = 73) responded. Overall, 66 respondents (90.4%) preferentially used hamstring tendon autografts. All surgeons estimated their retear rate to be ≤15%, with 31 (42.5%) <5%. Twenty-eight surgeons (38.4%) reported no benefit in preoperative rehabilitation. The majority of surgeons (82.2%–94.5%) reported that postoperative rehabilitation was important within various periods throughout the postoperative timeline. Most surgeons did not permit RTS until ≥9 months (n = 56, 76.7%), with 17 (23.3%) allowing RTS between 6 and 9 months. The most highly reported considerations for RTS clearance were time (90.4%), functional capacity (90.4%), and strength (78.1%). Most commonly, knee strength and/or function was assessed via referral to a preferred rehabilitation specialist (50.7%) or with the surgeon at their practice (11.0%). Conclusions: This survey revealed variation in beliefs and practices surrounding rehabilitation and RTS evaluation. This is despite the current evidence demonstrating the benefit of preoperative and postoperative rehabilitation, as well as the emerging potential of RTS assessments consisting of strength and functional measures to reduce reinjury rates.